Abundance of Plankton Population Densities in Relation to Bottom Soil Textural Types in Aquaculture Ponds (International Journal of Agricultural Research, Innovation and Technology, 2013)
Plankton is an important food item of fishes and indicator for the productivity of a water body. The present study was conducted to evaluate the effects of bottom soil textural conditions on abundance of plankton in aquaculture pond. The experiment was carried out using three treatments, i.e., ponds bottom with sandy loam (T1), with loam (T2) and with clay loam (T3). The ranges of water quality parameters analyzed were suitable for the growth of plankton during the experimental period. Similarly, chemical properties of soil were also within suitable ranges and every parameter showed higher ranges in T2. A total 20 genera of phytoplankton were recorded belonged to Chlorophyceae (7), Cyanophyceae (5), Bacillariophyceae (5), Euglenophyceae (2) and Dinophyceae (1). On the other hand, total 13 genera of zooplankton were recorded belonged to Crustacea (7) and Rotifera (6). The highest ranges of phytoplankton and zooplankton densities were found in T2 where low to mediumtype bloom was observed during the study period. Consequently, the mean abundance of plankton (phytoplankton and zooplankton) density was significantly highest in T2. The highest abundance of plankton in the T2 indicated that pond bottom with loamy soil is suitable for the growth and production of plankton in aquaculture ponds. DOI: http://dx.doi.org/10.3329/ijarit.v2i1.14006 Int. J. Agril. Res. Innov. & Tech. 2 (1): 56-61, June, 2012